2003
DOI: 10.1152/japplphysiol.00631.2001
|View full text |Cite
|
Sign up to set email alerts
|

Footstrike is the major cause of hemolysis during running

Abstract: There is a wide body of literature reporting red cell hemolysis as occurring after various forms of exercise. Whereas the trauma associated with footstrike is thought to be the major cause of hemolysis after running, its significance compared with hemolysis that results from other circulatory stresses on the red blood cell has not been thoroughly addressed. To investigate the significance of footstrike, we measured the degree of hemolysis after 1 h of running. To control for the potential effects of oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
179
2
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(202 citation statements)
references
References 25 publications
8
179
2
13
Order By: Relevance
“…Neonatal plasma FHb was followed for 1 week after being on ECMO, because it is a reliable measure of the degree of hemolysis. 5,6 Our findings that peak FHb was significantly lower in the unwashed blood group compared with the washed cohort during the first 3 days of ECMO, and that this difference disappeared on the 4th-7th day on ECMO, may have been due to the liver clearing the plasma of the excess FHb released by the washed cells. Therefore, using unwashed blood for ECMO may remove a subsequent added burden for the liver caused by transfused erythrocyte hemolysis.…”
Section: Discussionmentioning
confidence: 74%
“…Neonatal plasma FHb was followed for 1 week after being on ECMO, because it is a reliable measure of the degree of hemolysis. 5,6 Our findings that peak FHb was significantly lower in the unwashed blood group compared with the washed cohort during the first 3 days of ECMO, and that this difference disappeared on the 4th-7th day on ECMO, may have been due to the liver clearing the plasma of the excess FHb released by the washed cells. Therefore, using unwashed blood for ECMO may remove a subsequent added burden for the liver caused by transfused erythrocyte hemolysis.…”
Section: Discussionmentioning
confidence: 74%
“…As a result, intravascular hemolysis is thought to occur. Telford et al (16) have recently shown that foot strikes are the major contributor to hemolysis during running. In some workplaces, likewise, workers often hit their hands and palms repeatedly against hard objects via hand-transmitted vibratory tools.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the appearance of hemopexin in urine may indicate hemolysis during long-distance running. This degradation of erythrocytes is typical for endurance sports and especially longdistance running, which is explained by mechanical stress in the capillaries of the feet during running or oxidative and osmotic stress [22]. Furthermore, it was shown that changes in membrane proteins cause an increase in hemolysis [23].…”
Section: Comparison Of the Marathon Runners' Samples And The Control mentioning
confidence: 99%